ASSESSMENT OF CHARACTER AS A MAIN ASPECT IN THE IMPLEMENTATION OF PRUDENTIAL PRINCIPLES IN BRI'S MICRO BUSINESS CREDIT - Hadilla Maryati; Amelia Septiyani; Putri Agustin; Taupik; Eko Saputra Wijaya; Qoriatu Khoiroti Zikriatillah; Auggie Riandri Putri; Nanda Syafitri; Eva Sabrina (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
In carrying out its function as an intermediary institution, banks are required to apply the precautionary principle, in particular channeling funds through the provision of credit. In Article 29 Paragraph (2) of the banking law, Banks are required to maintain the Soundness level of the bank in accordance with the provisions on aspects of capital adequacy, asset quality, liquidity management, earnings, solvency and other aspects related to bank activities in accordance with the principle of prudence . The most important aspect in extending credit is the existence of a guarantee, especially material guarantees, it is urgent to apply the precautionary principle regulated in POJK NO 42/PJOK 03/2017 which requires banks to own and implement bank credit/financing policies.